Evaluating the performance of reclaimed asphalt pavement incorporating pelletRAP as a rejuvenator - Al-Saffar, Z. H.; Yaacob, H.; Mohd Satar, M. K. I.; Mohd Usak, S. N.; Putra Jaya, Ramadhansyah; Hassan, N. A.; Radeef, H. R.; Warid, M. N. M. (IOP Science, 2021)
In the recent years, the use of reclaimed asphalt pavement (RAP) in the pavement has become inevitable for economic and environmental reasons. However, the brittleness property of aged asphalt in the RAP restrict its usage in a high percentage. Nevertheless, the rejuvenators are introduced into the mixtures to reverse the effect of ageing processes, decrease the stiffness and increase the workability of RAP mixture. In the present research, various percentages of PelletRAP rejuvenator were added to 100% of RAP mixtures. The performance characteristics of rejuvenated mixtures were investigated via resilient modulus (MR), dynamic creep, and wheel tracking tests. The results showed that when the PelletRAP was included into the mixture, the MR values and the creep stiffness modulus (CSM) decreased, while the permanent creep, the creep strain slope (CSS) and the rutting depth increased. However, all the rejuvenated mixtures exhibited better results than that of virgin mixture. Such a trend of findings suggested that PelletRAP can be used as a rejuvenator without a negative effect on the high-temperature performance of asphalt mixtures.